(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
It is known that pesticides used in agricultural fields affect non-target organisms in the environment as they kill marine organisms or have negative effects on the vital organs of these organisms after entering the aquatic environment. Therefore, the aim of this study was to investigate the biochemical, histopathological, and genotoxic effects in trout (Oncorhynchus mykiss), and this was done by exposing the fish to sublethal concentrations of pyriproxyfen, imazamox, and hemixazole for 96 hours. Biochemical parameters of plasma samples, histopathological evaluation of gills, liver, kidneys, and spleen, and DNA damage of blood cells were investigated at 48 and 96 hours. The results showed that the levels of cholesterol, alkaline phosphatase, triglycerides, and total protein of fish exposed to higher concentrations of pyriproxyfen showed significant differences compared to the control group (P < 0.05). Regarding the histopathological effects of sublethal concentrations of pesticides, it was determined that the harmful effects on salmon increased depending on time and increasing concentration. Nuclear degeneration and necrosis in parenchymal cells were detected at an excessive level in the spleen. DNA strand breaks were also detected in the blood cells of fish depending on concentration and time. DNA damage was highest in fish exposed to high concentrations of pyriproxyfen, followed by imazamox and finally hemexazole. In conclusion, it was observed that the biochemical, histopathological, and genotoxic effects of pesticides increased depending on concentration and time. Therefore, during the use of these pesticides, we should be more careful to protect the aquatic environments.